2014
DOI: 10.1080/11356405.2014.935108
|View full text |Cite
|
Sign up to set email alerts
|

Digital illiteracy: a challenge for 21st century teachers / El analfabetismo digital: un reto de los docentes del siglo XXI

Abstract: In the light of different studies carried out at European and national level, it is unclear if the use of Information Society Technologies (ISTs) in the teaching-learning process is fulfilling initial expectations. Considering that teachers are the keystone upon which the required transformation is to be built, we consider the following questions: are teachers digitally illiterate? Do they have other reasons for not integrating ISTs in their classrooms? This research consists of a descriptive study of the teac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 18 publications
0
12
0
7
Order By: Relevance
“…The present moment urges the effective development of an educational model focused on learning assuming a great methodological and consequently cultural change, conforming a strategic plan with innovation proposals based on the emerging pedagogies, the consideration of good educational practices, the necessary teacher training, the social value, the development of the emotional competence and the ultimate consideration of shaping learning communities [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…The present moment urges the effective development of an educational model focused on learning assuming a great methodological and consequently cultural change, conforming a strategic plan with innovation proposals based on the emerging pedagogies, the consideration of good educational practices, the necessary teacher training, the social value, the development of the emotional competence and the ultimate consideration of shaping learning communities [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Por tanto, para dar respuesta a las nuevas necesidades de la realidad de la integración de las TIC en el ámbito educativo (Cabero, Roig y Mengual, 2017), los docentes han de desarrollar una competencia digital docente que les permita integrar las TIC de forma original, desde planteamientos no solo de adquisición de conocimientos instrumentales, sino interrelacionando contenidos, pedagogías y tecnologías. Esta alfabetización digital, adoptando nuevas competencias para mantener la educación de calidad (Cortina, Gallardo, Jiménez y Trujillo, 2014), es importante para que los docentes se desenvuelvan correctamente en la nueva forma de enseñar lo que la sociedad demanda, y esto se consigue aumentando la capacitación, fundamentalmente, en dos momentos: uno, en la formación inicial docente, en la que se deben adquirir todas las competencias que capaciten para el desempeño profesional docente; y, el segundo, en el proceso posterior de formación continua y permanente (García y Martín, 2016), necesario para la renovación y actualización continua de los docentes (Romero, Hernández y Ordóñez, 2016;Agreda, Hinojo y Sola, 2016).…”
Section: Introductionunclassified
“…In their study with non-university teachers, Cortina-Pérez, Gallardo-Vigil, Jiménez-Jiménez, and Trujillo-Torres (2014) found that more than 60 % of teachers made no use of Web 2.0 tools in their teaching work and, despite over 90 % of them having received ICT training, more than 70 % felt they were not prepared to make educational use of these technologies. In a recent study, again with non-university teachers, García-Pérez, Rebollo-Catalán, and García-Pérez (2016) showed that they have a moderate level of digital competence in the use of virtual social networks, but their digital competence for teaching is less developed.…”
Section: The Digital Competences Of Teachersmentioning
confidence: 99%